2022
DOI: 10.1590/2317-6431-2022-2660pt
|View full text |Cite
|
Sign up to set email alerts
|

Zumbido crônico: análise das contribuições clínicas de diferentes avaliações audiológicas

Abstract: RESUMO Objetivo Investigar se há diferenças nos achados audiológicos periféricos e centrais entre indivíduos com limiares auditivos normais com e sem zumbido crônico e, com isso, entender quais exames auditivos são importantes nessa população. Métodos A amostra foi composta por conveniência, incluindo indivíduos de 18 a 59 anos, divididos em dois grupos: grupo 1 (G1), formado por sujeitos sem queixa de zumbido crônico e grupo 2 (G2), por indivíduos com zumbido crônico. A avaliação consistiu nos seguintes pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
8

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 30 publications
1
4
0
8
Order By: Relevance
“…This study is in line with the specialized literature, since previous studies have shown the changes caused by the symptom of tinnitus in the CANS, which manifests itself in the functional capacity and, consequently, in the negative self-perception of these individuals, which may be correlated with speech decoding and comprehension (4,6,(17)(18)(19) . In addition, this study is pertinent due to the characteristics of the population studied, i.e.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study is in line with the specialized literature, since previous studies have shown the changes caused by the symptom of tinnitus in the CANS, which manifests itself in the functional capacity and, consequently, in the negative self-perception of these individuals, which may be correlated with speech decoding and comprehension (4,6,(17)(18)(19) . In addition, this study is pertinent due to the characteristics of the population studied, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the symptom causes changes in the neuroplastic functioning of the auditory pathway, which can impair functional capacity, negatively impacting speech understanding in this population (4) . Understanding these findings is of paramount importance for the speech therapy clinic, in order to reduce the damage to quality of life caused by tinnitus disorder, as well as to clarify whether this disorder really causes such difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations